Pelvic Rocking Exercise untuk Penurunan Nyeri Punggung Bawah pada Ibu Hamil Trimester III - Anna Sa'adah; Sri Sulistiyaningsih; Siti Marfu’ah (PROFESSIONAL HEALTH JOURNAL, 2023)
Back pain is a discomfort in pregnancy that occurs in almost all pregnancies. Treatment to reduce lower back pain in pregnant women is pelvic rocking. The purpose of this study was to determine differences in low back pain in pregnant women before and after pelvic rocking exercise intervention in Karangrejo Village, Juwana District. The type of research used was a pre-experiment with one group pretest posttest design. The population of this study was third trimester pregnant women in Karangrejo Village, Juwana District, Pati Regency, totaling 23 pregnant women. A sample of 20 pregnant women. The technique of this research is side purposive. The results of the Wilcoxon Signed Ranks Test were ρ value: 0.000 (p<0.05) there was a difference in lower back pain in pregnant women before and after pelvic rocking exercise intervention in Karangrejo Village, Juwana District. The suggestion of this research is that health workers are expected to apply non-pharmacological therapy, one of which is the pelvic rocking exercise technique.